2015
DOI: 10.2197/ipsjjip.23.58
|View full text |Cite
|
Sign up to set email alerts
|

Development of resource management server for production IaaS services based on OpenStack

Abstract: In this paper, we show the development of resource management server to enable production Cloud services easily based on OpenStack. In recent days, Cloud computing technologies have progressed and many providers have started Cloud services. Some providers use proprietary systems but others use open source IaaS software such as OpenStack and CloudStack. Because the community of OpenStack development is very active, we expect Open-Stack will become a de facto standard open source IaaS software. Because OpenStack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Users or operators request virtual resource controls to OpenStack via the GUI/API of the resource management server. Functions of resource management server are described in [7].…”
Section: Review Of Developed System and Methodsmentioning
confidence: 99%
“…Users or operators request virtual resource controls to OpenStack via the GUI/API of the resource management server. Functions of resource management server are described in [7].…”
Section: Review Of Developed System and Methodsmentioning
confidence: 99%
“…Keeping the concurrent processing number is for reducing negative impact on the actual user environments. Our previous work in cloud platform development [16] showed that more than three concurrent volume replications of OpenStack greatly affected storage.…”
Section: Performance Evaluation Of Automatic Verificationmentioning
confidence: 99%
“…[1], [2], [3]. IoT application areas are wide but in particular manufacturing and maintenance are regarded as the most likely application areas which Industrie 4.0 also targets.…”
Section: Introductionmentioning
confidence: 99%